Parental Gambling and the Health and Wellbeing of Children Derived From Two Nationally Representative Cohorts of Australian Children - Tulloch, Catherine; Hing, Nerilee; Browne, Matthew; Rockloff, Matthew; Hilbrecht, Margo (My University, 2022)
Gambling-related harms can impact the lives of children living with someone experiencing a gambling problem. These harms have been associated with impacts across a number of domains. However, previous studies exploring gambling-related effects on the health and wellbeing of children have had conflicting results. This study aimed to further understand the impact of parental gambling problems on children's health and wellbeing using nationally representative data from Growing up in Australia: The Longitudinal Study of Australian Children. The subsample of interest contained 3,695 children (49.1% female) across two cohorts aged around 12 and 16 years. Parental gambling problems were measured by the Problem Gambling Severity Index (PGSI). Child health and wellbeing was measured via the Child Health Utility 9D (CHU9D), the Spence Anxiety Scale, the Short Mood & Feelings Questionnaire, the Strengths and Difficulties Questionnaire (SDQ), and self-harm and happiness questions. Across both cohorts, the study found significant associations between parental gambling problems and poorer health, anxiety and/or low mood symptoms, and behavioural and emotional problems in children. The study found that more than 10% of Australian children were living in households with adults experiencing some level of gambling problems, including 1.2% in households with severe problems. Policymakers and educators might help ensure that the appropriate information and support is being provided to these children.
Applied Research in Quality of Life
Keywords: Families and relationships; Health and wellbeing